Cratojoppa maculata Cameron (Hymenoptera, Ichneumonidae, Ichneumoninae) new record to Malaysia - Norhafiza A.F.,; Idris A.B., (Pusat Sistematik Serangga, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2014)
Cratojoppa maculata is reported as new record to the fauna of Ichneumoninae from Malaysia. Five specimens was collected from malaise trap during field work sampling in Pasoh Forest Reserved in Negeri Sembilan between May 2002 until March 2003. The species was first time described by Cameron in 1907 based on specimen from Sikkim, India. The discovery of this species contributed to the fauna of the genus Cratojoppa in Malaysia apart from two species namely Cratojoppa ornaticeps and Cratojoppa maculiceps. In oriental region it has previously been found in China, India and Myanmar only. Key to three species of genus Cratojoppa found in Malaysia is provided.